Vocal Characteristics of Patients With Morbid Obesity - Bosso, Janaina Regina [UNESP]; Martins, Regina Helena Garcia [UNESP]; Pessin, Adriana Bueno Benito [UNESP]; Tavares, Elaine Lara Mendes [UNESP]; Leite, Celso Vieira [UNESP]; Naresse, Luiz Eduardo [UNESP] (Elsevier, 2019)
Introduction: Obesity modifies vocal characteristics, causing abnormal fat deposition in the abdominal region and upper airways. For some authors the voice of the obese is not different from nonobese and the vocal symptoms are scarce; for others dysphonia in obese is reported by 70% of them and the voice becomes hoarse, breathy, and unstable. Objective: To characterize the voice of patients with morbid obesity. Methods: Two groups were included: Obese (n-27), aged between 26 and 59 years, selected for bariatric surgery; Control (n-27), matched in age, with ideal weight for height. Parameters: Vocal self—assessment (Vocal Disadvantage Index—IDV and Quality of Life and Voice—QVV); Perceptual-auditory vocal evaluation (GRBASI scale), maximum phonation time; Acoustic vocal analysis and Videolaryngoscopic exams. Results: In obese, the most frequent symptoms were gastroesophageal and hoarseness. The vocal self-evaluation did not record any relevant complaints in both groups. In obese, the perceptual-auditory voice evaluations indicated significant changes in R (roughness), B (breathiness), I (instability), and S (tension) parameters. Acoustic vocal analysis recorded changes in the noise-harmonic ratio (NHR) and soft phonation index (SPI) parameters. The videolaryngoscopy examinations showed, in control and obese groups, respectively: normal: 92.5% and 55.5%; posterior pachydermia: 11.1% and 33.3%; mid-posterior bowing: 0% and 7.4%; edema/congestion: 0% and 7.40%. Conclusion: The voice of the obese becomes discreetly hoarse, breathless, and unstable. The most frequent videolaryngoscopic findings in obese patients are hyperemia and edema of vocal folds and posterior pachydermia, related to acid laryngitis, secondary to gastroesophageal reflux.
Keywords: Bariatric surgery—Dysphonia—Hoarseness—Obesity—Voice